ANALISIS PENGARUH PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN DAN KESEHATAN TERHADAP KEMISKINAN DI JAWA TIMUR - Naylal Fithri; David Kaluge (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2017)
Poverty is a complex issue because it relates to the inability of access to economic, social, cultural, political and participation in society became one assessment of the success of the government's performance. This study aims to determine the effect of government spending for education and health sector to poverty. The data used is secondary data with regression models panel.Hasil mneguunakan Research shows that the effect of government spending education sector and no significant negative effect on poverty. Government spending in the health sector and no significant positive effect on poverty. This is because the government is less effective in reducing the number of people living below the poverty line, this is evidenced by the tendency of increase in the number of poor people from time to time.